Pengembangan modul ajar menulis naskah drama satu babak Kurikulum Merdeka untuk peserta didik kelas XI SMK - Zahro, Azizatuz; Aprilia, Devi (Universitas Mulawarman, 2024)
This development study was conducted to create and make an independent curriculum-based teaching tool for trade school students in grade 11 that teaches them how to write play plots. The ADDIE model was used in this development research, which had five steps: analysis, design, development, implementation, and evaluation. This study led to the creation of an independent curriculum-based play script writing training program that both subject and practice experts have approved. Field tests were also done to see what the students learned and how they responded. The development study led to creating teaching modules that could be used for learning. These modules got scores of 94.22% from material experts and 96.44% from practitioner experts. The field test found that 50.8% of students learned what they were supposed to learn and that 93.3% of students responded. A score of 83.69% was found in the